Scattering Dynamics with Gaussian Potential in the Presence of a Bichromatic Laser Field - Das, Santosh Kumar; Dhobi, Saddam Husain (Api Journal of Science, 2025)
Scattering dynamics play a crucial role in understanding the fundamental interactions between particles and external fields. When a particle interacts with a target potential under the influence of an external laser field, its motion and energy distribution can be significantly modified. The aim of this work is to study the scattering dynamics of electron gaussian potential in presence of bichromatic linearly polarized laser fields. To fulfill the objective, we obtained S-matrix use Volkov wave equation and Gaussian potential with the help of Kroll-Watson approximation. Using relation of S-matrix and T-matrix, the obtained T-matrix which is directly related to differential cross section (DCS). The obtained DCS used to study the scattering dynamics of electron behavior with gaussian potential in laser field. The developed DCS equation was computed, the computed result shows DCS increases with increase of incidence energy of electron and becomes maximum and finally decreases. The DCS with photon energy is highly fluctuations and decrease with increase of scattering angle. The DCS of Bessel first order found greater than Bessel second order. These findings aid in laser-assisted collision studies, plasma diagnostics, nanomaterial design, and quantum device optimization by revealing electron behavior, multiphoton effects, and resonance control under bichromatic laser fields.